Phenotypic and Genotypic Spectrum of Children with Autosomal Recessive Hyperimmunoglobulin E Syndrome Caused by DOCK8 Mutation: A Systematic Review of Case Reports - Ananyan Sampath; Hemant Yadav; Sanjuna Juluri; Girish Chandra Bhat; Yogendra Singh Yadav (Wolters Kluwer Medknow Publications, 2024)
Background: Hyperimmunoglobulin E (IgE) syndrome (HIES) is a rare primary immunodeficiency disease, with features of recurrent eczema-like rashes, skin and lung infections, and elevated serum IgE. Common genetic mutations involve STAT3 and DOCK8 in autosomal dominant and recessive types, respectively. Objectives: Here, we aimed to systematically review all previously published case reports/series describing the clinical features, laboratory findings, and genetic analyses of children with autosomal recessive HIES (AR-HIES) caused by DOCK8 immunodeficiency. Methods: A comprehensive search was done in PubMed and Google Scholar, using defined search terms encompassing case reports or case series on AR-HIES. The identified reports underwent screening by different authors for inclusion and exclusion criteria. Results: A review of 50 articles covering 203 patients with DOCK8 immunodeficiency syndrome was done. Most cases were reported in countries such as Turkey, the USA, and Iran, with no significant gender disparity (92 males: 111 females). Patients exhibited a broad age range and early disease onset, with consanguinity present in 82% of cases. The most common clinical features included eczema (99%), allergic manifestations (93%), and respiratory infections (91%), associated with high IgE levels and eosinophilia. Exonic deletions were the most common mutations. Conclusion: This is one of the largest reviews collating data on DOCK8 deficiency, leading to AR-HIES. Exonic deletions were the most common mutations, with eczema and allergy being the most consistent clinical features.